Сучасні регіональні студії та суспільні комунікації: макроекономічний аспект - Губанова, Ніно Нодарівна; Яцина, Вікторія Валентинівна; Коротун, В. С. (Український державний університет залізничного транспорту, 2025)
В умовах глобалізації та посилення міжрегіональної конкуренції особливої актуальності набувають дослідження чинників та механізмів підвищення конкурентоспроможності регіонів, їх здатності генерувати та впроваджувати інновації, залучати інвестиції та кваліфіковані кадри. Макроекономічний аспект цих процесів полягає у вивченні впливу загальнонаціональних економічних трендів, політик та інституційних рамок на розвиток окремих регіонів, а також у дослідженні зворотного впливу регіональної динаміки на макроекономічну стабільність та зростання країни загалом. In the context of globalization and intensified interregional competition, the study of factors and mechanisms that enhance regional competitiveness is becoming increasingly relevant. This includes analyzing the ability of regions to generate and implement innovations, attract investments, and secure highly qualified human resources. The ability of a region to adapt to changing economic conditions, integrate into global value chains, and foster an innovative business environment plays a crucial role in determining its long-term success and sustainability. The macroeconomic aspect of these processes involves examining how national economic trends, policies, and institutional frameworks influence the development of individual regions. Government policies related to taxation, infrastructure investment, labor market regulations, and technological advancement shape the competitive advantages of regions and their ability to drive economic growth. Additionally, financial incentives, regional development programs, and digital transformation strategies contribute to enhancing local economic resilience and fostering sustainable development. At the same time, it is essential to study the reverse impact of regional dynamics on the overall macroeconomic stability and growth of the country. Economic disparities between regions, differences in resource availability, and variations in industrial specialization can create both opportunities and challenges for national economic stability. Highly developed and innovation-driven regions often serve as growth engines, generating employment and contributing to national GDP, while less developed regions may struggle with economic stagnation and demographic decline. Furthermore, globalization and digitalization are reshaping traditional regional economies by enabling new forms of cooperation, remote work, and cross-border investments. The emergence of smart cities, digital hubs, and knowledge-based economies emphasizes the importance of regional adaptability and strategic planning. In this context, ensuring an effective balance between national-level economic strategies and regional autonomy is key to promoting inclusive and sustainable growth. Effective regional policies must integrate elements of economic diversification, infrastructure modernization, education and workforce development, as well as environmental sustainability. Strengthening institutional capacity, enhancing interregional cooperation, and leveraging public-private partnerships are crucial for maximizing the potential of each region and ensuring a balanced and resilient national economy.
Modern regional studies and public communications: macroeconomic aspect
Keywords: макроекономічний аспект; супільні комунікації; регіональні студії; резильєнтність; цифровізація; macroeconomic aspect; joint communications; regional studies; resilience; digitalization